PEDAGOGICAL CONDITIONS OF ORGANIZING INDEPENDENT LEARNING ACTIVITIES IN HIGHER EDUCATION - Erkinov, Bobirbek (International Conference on Business & Management, 2026)
This article provides an in-depth analysis of the scientific and theoretical foundations of organizing students’ independent learning activities in the higher education system. The essence and content of independent learning, its didactic principles, pedagogical conditions, and its close relationship with modern educational paradigms are examined. Furthermore, the role and significance of the competency-based approach, learner-centered education, and digital educational technologies in developing students’ independent knowledge acquisition skills are scientifically substantiated.